Incidence of Acute Kidney Injury and Associated Mortality among Individuals with Drug-Susceptible Tuberculosis in Uganda - Kansiime, Grace; Aklilu, Abinet M.; Muzoora, Conrad K.; Baluku, Joseph Baruch; Wilson, F. Perry; Bajunirwe, Francis; Kanyesigye, Michael; Brewster, Ursula; Kalyesubula, Robert (Kidney360, 2024)
Background: Although tuberculosis (TB) is associated with significant mortality and morbidity, its impact on kidney function is not well understood and is often attributed to anti-TB drugs. We aimed to assess the incidence of AKI in the immediate post-TB diagnosis period in Uganda, a TB/HIV-endemic country in sub-Saharan Africa. Methods: We included patients enrolled in an observational cohort study of adults diagnosed with drug-susceptible TB followed longitudinally. Adults ($18 years) without known kidney disease were enrolled between August 2022 and July 2023 at three regional hospitals serving 12.5% of the Ugandan population. Our primary outcome was incidence of Kidney Disease Improving Global Outcomes-defined AKI within 2 weeks of TB diagnosis. Other outcomes included predictors of AKI and its association with 30-day survival. Results: A total of 156 adults were included. The median age was 39 (interquartile range, 28–53) years, most patients were male (68.6%), and 49.4% had HIV. People with HIV had shorter time to TB diagnosis from symptom onset (21 days; interquartile range, 7–30) compared with HIV-negative participants (60 days; interquartile range, 23–90), P< 0.001. The incidence of AKI was 33.3% (52/156) and was similar between people with and without HIV. Proteinuria or hematuria at enrollment was associated with higher odds of AKI (odds ratio, 2.68; 95% confidence interval, 1.09 to 6.70; P approximately 0.033). AKI was associated with a significant risk of mortality (adjusted hazard ratio, 8.22; 95% confidence interval, 1.94 to 34.72; P approximately 0.004) independent of HIV status. Conclusions: The overall incidence of AKI in the immediate post-TB diagnosis period is high and associated with increased mortality risk. Our findings suggest that monitoring kidney function should be routine for patients with TB, including before treatment initiation.
Keywords: AKI; Mortality; Tuberculosis; Uganda